1995
DOI: 10.1084/jem.182.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutations in immunoglobulin heavy chain variable region genes of microdissected marginal zone (MGZ) B cells suggests that the MGZ of human spleen is a reservoir of memory B cells.

Abstract: SummaryThe splenic marginal zone (MGZ), which surrounds the mantle zone (MTZ) in human splenic white pulp, contains a phenotypically and morphologically distinct population of B cells. The origin of MGZ B cells is .uncertain. Whereas some experiments in rodents have suggested that they are a distinct cell lineage responsible for the immune response to T-independent type 2 antigens, others have suggested that they are memory B cells derived from a germinal center (GC) response. The progeny of a GC reaction is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(199 citation statements)
references
References 37 publications
15
181
3
Order By: Relevance
“…This datum coincides with others previously obtained in the analysis of the IgV H and bcl-6 genes, which corroborate that mantle cells in the spleen are naive B cells. 16 The data presented here seem to support the hypothesis that, in spite of initial morphological observations, a significant proportion of SMZL cases could derive from an unmutated naive precursor other than the marginal zone, and possibly situated in the mantle zone of the splenic lymphoid follicles. This is consistent with the high frequency of IgD expression by SMZL cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This datum coincides with others previously obtained in the analysis of the IgV H and bcl-6 genes, which corroborate that mantle cells in the spleen are naive B cells. 16 The data presented here seem to support the hypothesis that, in spite of initial morphological observations, a significant proportion of SMZL cases could derive from an unmutated naive precursor other than the marginal zone, and possibly situated in the mantle zone of the splenic lymphoid follicles. This is consistent with the high frequency of IgD expression by SMZL cells.…”
Section: Discussionsupporting
confidence: 75%
“…These findings confirm previous data on the frequency of IgV H mutations in the marginal zone cells of the spleen, thereby confirming that at least a significant proportion of splenic marginal zone B cells are composed of memory cells, which is consistent with their IGM + IgD − immunophenotype, suggesting that these cells are post-germinal center B cells (Table 3). 16,18 This study has also shown evidence of clonal expansion within the marginal zone. However, the mantle cells of the spleen that were analyzed, selected on the basis of their IgD expression, show a germinal configuration of the bcl-6 gene.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Hence, when looking at the immunoglobulin gene rearrangements in a sample, the presence of mutations, in comparison to germline sequences, makes it evident that the cell has been activated by antigen. Thus, we could show for the first time that even though the B cells of the splenic marginal zone were not class switched, retaining IgM functionality, they were still antigen‐experienced cells as their Ig genes were mutated 20. In chronic lymphocytic leukemia (CLL) the extent of mutation was investigated to try and understand the etiology of the disease and it was found that there were two different classes of CLL with prognostic significance, those with mutated immunoglobulin genes and those carrying germline immunoglobulin genes 21.…”
Section: Generation Of B Cell Diversitymentioning
confidence: 96%
“…It also potentially biased the measurements of J region usage and was open to the risk of V region bias due to faulty primers by virtue of the fact that the V region primers were a mix of family‐specific primers. While these early sequencing technologies were invaluable for the discovery of new cell populations, they often relied on expensive and time‐consuming cloning that did not capture the full repertoire; due to the single channel capabilities of Sanger Sequencing 20, 22, 29, 58…”
Section: Repertoire Analysis Approachesmentioning
confidence: 99%